Antimicrobial ingredients affect beef snack stick quality - A.L. Mayer; J.A. Gunderson; A.S. Lobaton-Sulabo; Elizabeth A.E. Boyle; Terry A. Houser; James J. Higgins (Kansas Agricultural Experiment Station Research Reports, 2008)
The Centers for Disease Control and Pre- vention estimate that 2,500 people become infected with listerosis each year by consuming food containing Listeria monocytogenes. Certain ready-to-eat meat and poultry products, particularly deli meats and hot dogs, are considered high risk products based on a Listeria risk assessment performed by the Centers for Disease Control and Prevention, the U.S. Food and Drug Administration, and the U.S. Department of Agriculture Food Safety and Inspection Service. Meat and poultry processors use various strategies to minimize L. monocytogenes contamination in ready-to-eat products; one strategy is inclusion of antimicrobial ingredients. Meat snacks, including snack sticks, are popular items in the United States; $3 million of meat snacks were sold in the United States during 2007. However, these snacks typically are not produced with antimicrobial ingredients. Ional2, Ional LC, and PURSAL Opti.Form PD43 are three organic acid salts that can be added to product formulations to limit L. monocytogenes growth. Ional contains buffered sodium citrate, and Ional LC is a combination of buffered sodium citrate and sodium diacetate that is optimized for L. monocytogenes control. Opti.Form contains sodium lactate and sodium diacetate. Inclusion of buffered sodium citrate is limited by the USDA Food Safety and Inspection Service to 1.3% in a formulation, but higher levels might be needed for effective L. monocytogenes control. Our objective was to evaluate quality characteristics and consumer preference of beef snack sticks formulated with these three antimicrobial ingredients.
Keywords: Cattlemen' s Day; 2008; Kansas Agricultural Experiment Station contribution; no. 08-212-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 995; Beef; Cattle; Snack stick